Meaning and etymology: on Greek χρεών and εἵλωτες, and on a rediscovered Euripidian form, διχαστήρ or διχαστής (Ion, 1156) (Atti del Sodalizio Glottologico Milanese, 2021)
Meaning and etymology: on Greek χρεών and εἵλωτες, and on a rediscovered Euripidian form, διχαστήρ or διχαστής (Ion, 1156). We examine three difficult cases where semantics, etymology and text establishment are implicated and where thorough analysis in one of these specialities helps to progress in the others. First, we show that semantics is opposed to the reading χρεῶν in the Hippocratic oath. In fact, we must recognize another word, χρεών, cf. χρή. For the second word, the name for hilots, what is meant is clear, but the etymology is not established. The studies on the archaic structure of Greek perfect lead us to bring forward an explanation: the word εἵλωτες goes back to an old perfect participle with zero vocalism, without the κ-affix. Last of all, it happens sometimes that a word has been corrupted in the mauscript tradition (Eur. Ion, 1156 †διχήρης). If context is enough explicit, so that the word’s sense is clear, to-day linguistic science allows to bring forward a restoration based not upon one’s intuition, but on language’s great morphological processes (διχαστήρ or διχαστής). Combining these various approaches will lead us to progress in the field of lexicography and etymology of the vocabulary in the ancient languages.